Effects of Root Cooling on Plant Growth and Fruit Quality of Cocktail Tomato during Two Consecutive Seasons. (25th September 2019) - He, F.; Thiele, B.; Watt, M.; Kraska, T.; Ulbrich, A.; Kuhn, A. J.
Abstract : Understanding the effects of root temperature on plant growth and key food components of horticultural crops under greenhouse conditions is important. Here, we assess the impact of root cooling on plant growth and fruit quality of two cocktail tomato cultivars ( Lycopersicon esculentum cv "Amoroso" and cv "Delioso") during the winter of 2017-2018 and the summer of 2018. Plants were grown hydroponically on rockwool under different root temperatures (16–27°C and 10°C) from the 2 nd inflorescence to harvest inside the greenhouse. A root temperature of 10°C was controlled independently from air temperature (18–23°C in winter and 21–29°C in summer) by circulating cooling water. Reductions of marketable yield per plant (7.9–20.9%) in both cultivars were observed in response to root cooling in winter, but not significantly in summer. In most cases, root cooling had a positive effect on the functional quality (sugars, vitamin C, and carotenoids levels). In the case of "Delioso, " glucose concentration increased by 7.7–10.3%, vitamin C by 20–21%, and lycopene by 16.9–20.5% in both seasons. "Amoroso" exhibited only higher consistent values in glucose with increments between 6.9 and 7.8% in the two seasons. The levels of elements decreased by root cooling, with statistically significant reduction of N, P, S, and Fe by 12.1–15.7% in "Delioso" in winter and P and Zn by 9.1–22.2% in both cultivars in summer. Thus, manipulation of root temperature could be a feasible method to improve the overall fruit quality of cocktail tomato; however, this effect was also dependent on cultivars and other environmental factors.